Pengaruh Kualitas Pelayanan Dan Promosi Terhadap Kepuasan Pelanggan OVO (Studi Kasus Pada Mahasiswa STIE Eka Prasetya) - Sri Rezeki; Desma Erica Maryati M; Muammar Rinaldi (LPPM STIE EKA PRASETYA, 2020)
The purpose of this study is to determine the effect of Service Quality and Promotion on OVO Customer Satisfaction. The research methodology used is quantitative descriptive method, the unit of analysis in this study is STIE Eka Prasetya and the observation unit is students from STIE Eka Prasetya. The population in this study were 993 respondents from STIE Eka Prasetya. The technique of determining the number of samples used in this study is the Slovin formula and amounted to 91 respondents. The research method used is the technique of data collection through the distribution of questionnaires that conducted systematically based on research objectives. The analytical method used to solve problems and prove hypotheses is descriptive analysis and regression analysis. This analysis includes validity and reliability, classic assumption tests, multiple linear regression analysis, hypothesis testing through t and F tests, and the coefficient of determination (R2) test. The results of the t test show that the variable Service Quality has a positive and significant effect on OVO Customer Satisfaction, and the Promotion variable has a positive and significant effect on OVO Customer Satisfaction. The results of the F test show that the Service Quality and Promotion simultaneously effect the Customer Satisfaction. The result of coefficient of determination test results (R2) shows that Customer Satisfaction was effected by Service Quality and Promotion variables, while the remaining is explained by other variables such as perception, digital marketing and personal selling that are not discussed in this study.